?DELIGNIFICATION OF KENAF (HIBISCUS SABDARIFFA) BY ORGANOSOLV PULPING PROCESS. PART-II. FORMIC AND PROPIONIC ACIDS (Biological Sciences - PJSIR, 2000)
Organosol v delignification of kenaf (Hibiscus sabdariffa) mediated by formic and propionic acids, catalyzed by hydrochloric acid, was evaluated. The effect of different variables like concentrations of acid and catalyst and charge ratios on the yield and quality of the delignified products alongwith the kinetics of delignification process was studied. It was, thereafter, established that optimum conditions of delignification of kenaf for these two acids were 80 and 90% concentration (w/w) of acid, 0.2% of catalyst, solid-liquor ratio of I: 12.5 and fractionation time of 120 and 90 minutes for formic and propionic acids, respectively. Furthermore, it was observed that propionic acid gives comparatively a better quality delignified product in good yield and takes lesser time as compared to the other aliphatic organic acids.